SOSOK DOSEN IDEAL DALAM PERSPEKTIF GEN Z PRODI PENDIDIKAN AGAMA ISLAM ANGKATAN 2023 FAKULTAS TARBIYAH DAN KEGURUAN UIN ANTASARI BANJARMASIN - Surawardi, Surawardi; Saputri, Annaya Nur; Zahrah, Annisa; Mauijah, Assyifaul; Anugrah, Muhamad Ridha; Rizqianto, Muhammad Hirzi (STAI AL FALAH Banjarbaru, 2025)
Abstract This study aims to describe students' views on the ideal lecturer figure in the context of higher education. Based on the results of interviews with several respondents, it was found that the ideal lecturer is described as a figure who is motivating and inspiring, charismatic and professional, interactive in delivering material, adaptive to the development of the times, humanistic and not a